Indicadores financeiros determinísticos do confinamento de bovinos no RS - Leal, Willian Silveira (2015)
The objective of this study was to evaluate the economic viability of feedlot finished steers and young steers, through the use of financial indicators evaluated together in order to facilitate decision making. Dissertations data were used, theses and scientific papers, conducted in the Beef Cattle Laboratory of UFSM. Was collected there maining period of data in feedlot, average daily gain,feed conversion, initial and slaughter weight, carcass weight and fat thickness. After collecting the data were tabulated and the mean with the help of spreadsheet, to make it possible to simulate a containment scenario, where the young steers remain in feedlot for 151 days and steers for 75 days. Were calculated diets according to the nutritional needs and feed conversion observed in the collected works, and from the cold carcass weight data and subcutaneous fat thickness categories were embedded in bônus categories were calculated, and the Young steers received about 7% the price paid for animal fat and steers received 8%. Fort he estimation of production costs and economic indicators we used the deterministic method, assuming fixed values (known) for the componentes of the costs and economic indicators. The higher implementation costs were the purchase of lean animal and food (forage + concentrate). The purchase of lean animal represented 73.26% of variable costs for the young category, since for young steers this item represented 48.33%, this decrease was due to the increase in the share of food costs in the latter category (24.91% of costs forage and 21.41% concentrate costs). The young steers slaughter category showed negative income (R$ -153.22 animal-1 for non-bonus and R$ -38.20 animal- 1 for bonus). Young steers had a positive income of R$ 56.16 and 215.59, respectively. Among economic indicators, the Net Present Value (NPV) shows that it is possible to recover the initial investment made for the young category, regardless of the bonus.Young steers the NPV is negative, regardless of the bonus. The Index Benefit Cost (IBC) was R$ 0.93 for the young steers not bonus and R$ 1.00 for the bonus. Young animals obtained IBC R$ 1.04 for non-bonus and R$ 1.14 for the bonus. The Additional Return on Investment (ROIA) was negative for young steers independently of the bonus, since for steers this indicator showed values of 1.45% for non-bonus and 4.42% for bonus. The Internal Rate of Return for the young steers was -2.61% for non-bonus and bonus to -0.37. For young steers the IRR was 3.76% for non-bonus and 13.01% for bonus. The use of these two indicators together shows that the slaughter of young steers is associated with the risk for this value're both Attractiveness Minimum rate (0.5965%) and, finally, the discounted payback presented higher values than the feedlot time of animals for both categories, indicating that the activity is high risk.